Assessing the utility of a novel terrestrial biodiversity quality indicator with 10 years of monitoring data. (February 2018) - McKenzie, Theresa; Normand, Lionel; Iwanycki, Natalie; Miller, Gavin; Prior, Paul
Highlights: We present a conservation concern-weighted indicator species score (ISS). We assess the ISS using 10 years of monitoring data for 50 indicator species. The ISS responds to landscape-level habitat predictors and to urban impacts. The ISS supports conservation management target-setting, and benchmarking. The ISS is intuitive and easily communicated to non-scientific audiences. Abstract: We introduce a novel terrestrial biodiversity quality index developed to inform conservation management at a regional/local scale. Our index, the indicator species score (ISS), is derived from data for indicator birds, amphibians, mammals, plants and lichens representative of the major landscape-scale habitat types in the region and a range of sensitivities to urbanization. The ISS incorporates the conservation concern scores of the species monitored. We assess the practical utility of the ISS using 10 years of data for 50 indicator species monitored at 54 fixed sites in the Toronto region, Ontario, Canada. We test the sensitivity of the ISS to temporal and spatial differences/trends. We assess its responsiveness to landscape-level habitat size and quality predictors including natural cover area and wetland area within 500 m, 1 km, and 2 km of the monitoring site centroid, as well as habitat patch score, and road density. We investigate the utility of the ISS in modelling landscape-level effects. We find that it responds to the habitat predictors, to road density and to urbanization impacts other than those tested. We conclude that the ISS supports ecologically relevant interpretation and management target setting/benchmarking. It is intuitive in nature, easily communicated to a non-scientific audience and therefore useful for management reporting. ISS results following 10 years of monitoring also lead us to consider the relative importance of the many impacts that urbanization exerts on areas of natural cover that remain within an urban matrix. We recognize the need to develop metrics, where possible, in order to quantify individual impacts, monitor them, and establish priorities for the reduction or mitigation of the specific drivers of biodiversity quality decline.